Problematyka społecznej odpowiedzialności w nauczaniu historii biznesu w Harvard Business School - Jastrząb, Mariusz (Annales. Etyka w Życiu Gospodarczym, 2013)
Based on case studies prepared at the Harvard Business School, the article analyses the content of university courses on business history. Its aim is to answer the question whether or not business history courses are used for discussing the problems of CSR or moral dilemmas behind strategic decisions made by managers. The article argues that the chance of enhancing the understanding of social problems on the part of the managers and shaping their responsiveness to them, created by the presence of courses on history in the academic curriculum, remains, to a large extent, unrealised. Teaching materials are still influenced by the Chandlerian paradigm and thus focus on changes in organisational structures and strategies of large multinational companies. They pay little attention to the social environment of business, rarely pose questions on the motivations of human actions or value hierarchies and avoid discussions on the social consequences of management decisions.